2023
DOI: 10.3390/plants12091755
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chloroplast Microsatellite Markers and Evaluation of Genetic Diversity and Population Structure of Cutleaf Groundcherry (Physalis angulata L.) in China

Abstract: Cutleaf groundcherry (Physalis angulata L.), an annual plant containing a variety of active ingredients, has great medicinal value. However, studies on the genetic diversity and population structure of P. angulata are limited. In this study, we developed chloroplast microsatellite (cpSSR) markers and applied them to evaluate the genetic diversity and population structure of P. angulata. A total of 57 cpSSRs were identified from the chloroplast genome of P. angulata. Among all cpSSR loci, mononucleotide markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…SSRs are widespread throughout plastid genomes across different species and are extensively employed in plant population studies [58][59][60]. In this study, the identified SSRs varied in number, with counts ranging from 198 in C. nitrarium to 208 in C. dzhungaricum plastomes, resulting in a total of 814 SSRs (Table 4).…”
Section: Discussionmentioning
confidence: 87%
“…SSRs are widespread throughout plastid genomes across different species and are extensively employed in plant population studies [58][59][60]. In this study, the identified SSRs varied in number, with counts ranging from 198 in C. nitrarium to 208 in C. dzhungaricum plastomes, resulting in a total of 814 SSRs (Table 4).…”
Section: Discussionmentioning
confidence: 87%
“…P. angulata is applied as a traditional folk medicine to cure sore throats, coughs, rheumatism, and hepatitis in many countries, including China, Mexico, Indonesia, and Brazil . The fruits, a sweet or tasteless berry-type climacteric fruit, are known as wild tomato, winter cherry, and gooseberry. A previous study on its whole plant generated a variety of withanolide derivatives, which exhibited cytotoxic and good anti-inflammatory activities. ,, UPLC-Q-Orbitrap-MS/MS was used for the first time to study bioactive withanolides from the fruits of P.…”
Section: Discussionmentioning
confidence: 99%
“…SSRs are co-dominant, multi-allelic, highly polymorphic, and have been widely used in various fields, including genetic diversity, phylogenetic studies, molecular identification, and genetic mapping ( Poczai et al., 2013 ). Several SSR markers have been developed and extensively utilized in the investigation of genetic diversity within Physalis species ( Simbaqueba et al., 2011 ; Wei et al., 2012 ; Delgado-Bastidas et al., 2019 ; Feng et al., 2023 ). In a study by Delgado-Bastidas et al.…”
Section: Genetic Diversitymentioning
confidence: 99%